Hearing loss in relation to sound exposure of professional symphony orchestra musicians - Schmidt, Jesper H; Pedersen, Ellen R; Paarup, Helene M; Christensen-Dalsgaard, Jakob; Andersen, Ture; Poulsen, Torben; Bælum, Jesper (Ear and hearing, 2014)
The objectives of this study were to: (1) estimate the hearing status of classical symphony orchestra musicians and (2) investigate the hypothesis that occupational sound exposure of symphony orchestra musicians leads to elevated hearing thresholds. The study population comprised all the musicians from five symphony orchestras. Questionnaires were filled in by 337 subjects, and 212 subjects performed an audiometric test. For a group of 182 musicians (363 ears) the results of the audiometry was analyzed in relation to the individual exposure, which was estimated on the basis of sound measurements and questionnaire data regarding the exposure time. The mean hearing threshold at the frequencies 3, 4, and 6 kHz, corrected for age and sex, was used as outcome. The musician ears with the highest exposure (29 of 363) had an additional threshold shift of 6.3 dB compared with the 238 ears with lowest exposure. The observed hearing loss of musicians was smaller compared with the noise-induced permanent threshold shift (NIPTS) predicted from ISO1999. A remaining confounding effect of age after ISO7029 age corrections could be observed to explain the difference in observed and predicted NIPTS. However, the observed hearing loss difference between the left and the right ear of musicians was 2.5 dB (95% confidence interval 1.5-3.6), which was similar to the NIPTS predicted from ISO1999. Most of the musicians had better hearing at 3, 4, and 6 kHz for age than expected, however, 29 ears with the highest exposure above 90.4 dBA with a mean exposure time of 41.7 years had significantly elevated hearing thresholds. Trumpet players and the left ear of first violinists had significantly elevated hearing thresholds compared with other musicians. Most of the symphony orchestra musicians had better hearing than expected but they had a work-related risk of developing additional noise-induced hearing loss. The additional NITPS of the left ear compared with the right ear was at the expected level based on the cumulated sound exposure and ISO1999, indicating that performing music may induce hearing loss to the same extent as industrial noise.